Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content:• Assess the Performance of Secondary School Principals in Jeddah to Achieve Saudi Arabia's Vision Targets Accordance with the Hellinger's Measure From Teachers View pointsMs. Rogaiae Faisal Fadhil* ,Ms. Abrar Housain ALthabiani ,Prof. Hayat Mohammad Saad Alharbi• Smart Supervision for School Empowerment and Educational Performance Improvement:  A Study in Saudi Public EducationMs. Maryam Abdullah Al-Luhaidan ,Ms. Mashael Aseer Al-Otaibi• The Technical readiness for Applying Modern Syllabus of Science at the Secondary Stage in Taif GovernorateMr. Abdullah Jaza Fayhan Al-Nafie• Degree of  Public  School Practice Total Quality Standards Central Gaza Strip, and Relationship  to Educational Strategic Planning Effectiveness from Teachers' ViewMs. Sabreen Salman Mezyed, Co-Prof. Suleiman Hussain Al Muzayn• The Role of Community-Based Educational Initiatives in Sustaining Education During the Israeli Aggression on Gaza: A Parental PerspectiveDr. Nael Hassan Adwan ,Mr. Subhi Rabee Shuaib• Strategic Leadership as a Contemporary Trend in Educational Institutions: An Analytical Study of the Concept, Dimensions, and Challenges in the Kingdom of Saudi ArabiaMs. Sarah Ajlan Al-Shahri• Validation of the World Health Organization's Abbreviated Quality of Life Scale on a Sample of Children with Cancer at Rambam Hospital in Haifa، Palestinian TerritoriesMr. Adnan Mahmoud Otallah
Keywords: Journal of Educational and Psychological Sciences